Digital signal processing : fundamentals and applications - Tan, Lizhe, 1963-; Jiang, Jean (Academic Press, an imprint of Elsevier, 2019)
"Digital Signal Processing: Fundamentals and Applications, Third Edition, not only introduces students to the fundamental principles of DSP, it also provides a working knowledge that they take with them into their engineering careers. Many instructive, worked examples are used to illustrate the material, and the use of mathematics is minimized for an easier grasp of concepts. As such, this title is also useful as a reference for non-engineering students and practicing engineers. The book goes beyond DSP theory, showing the implementation of algorithms in hardware and software. Additional topics covered include adaptive filtering with noise reduction and echo cancellations, speech compression, signal sampling, digital filter realizations, filter design, multimedia applications, over-sampling, etc. More advanced topics are also covered, such as adaptive filters, speech compression such as PCM, µ-law, ADPCM, and multi-rate DSP, over-sampling ADC subband coding, and wavelet transform." --sciencedirect.com